New species of Pseudoscorpiones (Arachnida) from tree hollows in a Mediterranean oak forest in Spain - Hernández-Corral, Jesús; Zaragoza, Juan A.; Micó, Estefanía (Zootaxa, 2018)
Pseudoscorpions inhabiting mature Quercus pyrenaica Willd. trees have been surveyed using hollow emergence traps and window traps in Salamanca, Spain. Three new species are described: Neobisium (N.) hispanicum Zaragoza & Hernández-Corral, n. sp., Rhacochelifer gaeli Zaragoza & Hernández-Corral, n. sp. and Rhacochelifer nonidezi Zaragoza & Hernández-Corral, n. sp. The genera Amblyolpium Simon, 1898 and Beierochelifer Mahnert, 1977 and the species Amblyolpium dollfusi Simon, 1898 and Beierochelifer peloponnesiacus (Beier, 1929) are new records for the Iberian Peninsula. Beierochelifer peloponnesiacus jonicus (Beier, 1932) is shown to be a junior subjective synonym of B. peloponnesiacus n. syn. New regional records of five other species belonging to the families Cheliferidae, Chernetidae and Withiidae are given. Keys are given for the species of the genera Pseudorhacochelifer Beier, 1976 and Rhacochelifer Beier, 1932 with elongated keels on posterolateral corners of carapace and anterior tergites in males, and for the Rhacochelifer species of the Iberian Peninsula. Complementary data to the description of the female syntypes from Caravaca (Murcia, mainland Spain) and males from the Canary Islands of Rhacochelifer pinicola (Nonídez, 1917) are given. Brief redescriptions of the female of Neobisium (N.) maroccanum Beier, 1930 and the male of Rhacochelifer euboicus Mahnert, 1977 are provided. The previous record of R. disjunctus from Slovakia is shown to be an error for R. euboicus. New data on the distribution and habitats of species of Cheliferidae, Chernetidae and Withiidae are given.